Emulation and technological adaptation in late 18th century Cloisonné-style Chinese painted enamels - Norris, Dana; Braekmans, Dennis; Shortland, Andrew J. (Wiley, 2022)
Cloisonné-style motifs are rare and enigmatic in Chinese painted enamels because of their distinct technological development at the end of the 18th century. Five late Qianlong to Jiaqing period (1736–1820) Chinese painted enamels with cloisonné-style motifs are investigated using environmental scanning electron microscopy–energy dispersive X-ray spectroscopy. Back-scattered electron images and elemental analysis are combined to study the decorative enamelled surface. The compositions of the layers within the enamel, that of the counter enamel and the polychrome decoration on the surface are determined and identified. Fluorine and elevated amounts of calcium were detected, indicating that fluorite was likely used as a raw material. The presence of this mineral, which is typical of Chinese cloisonné, confirms that these objects share both aesthetic and technological relationships.
Keywords: Canton enamel; cloisonné; enamelled metal; ESEM-EDX; glass; overglaze; porcelain